Influence of School Leadership to Development BTQ Students - Farhah, Nayla; Taqiyuddin, Taqiyuddin; Rusman, Maman (IAIN Syekh Nurjati Cirebon, 2020)
Principals' leadership which can be interpreted as the way or effort of the principal in influencing, encouraging, guiding, directing and moving the behavior of others and making a change in more positive direction in seeking the quality and success of educational goals. The principal carries out his duties and responsibilities as a leader, how the role of the principal will greatly influence the development of the Qur'anic learning process at school.This study aims to examine the influence of school principal leadership on the development of Al-Qur'an Reading (BTQ) students in the Nahdlatul Ulama Vocational High School (SMK NU) Raudlatul Muta’allimin Singaraja Indramayu. This research method is quantitative. The study population was all students of SMK NU Raudlatul Muta’allimin Singaraja Indramayu in the academic year 2018/2019 which were 123 students. From this population, 32 students were selected to be sampled with stratified random sampling technique. Data collection techniques using the method of observation, interviews, questionnaires and documentation. The results showed that the principal's leadership significantly influenced the development of reading and writing Al-Qur'an (BTQ) students at SMK NU Raudlatul Muta’allimin Singaraja Indramayu. Keywords: Leadership, Headmaster, Reading and Writing the Qur’an.